Association of Irisin Circulating Level with Diabetic Retinopathy: A Case-Control Study - Tarboush, Nafez Abu; Abu-Yaghi, Nakhleh E; Al Ejeilat, Laith H; Wahed, Rawand K. Abdel; Jeris, Issa N (Experimental and Clinical Endocrinology & Diabetes, 2018)
Obesity and obesity induced type 2 diabetes development and progression have been associated with sedentary lifestyle. Irisin, a newly discovered myokine, has been demonstrated at lower levels in obese and type 2 diabetes patients compared to controls. The main aim of this study is to explore association of Irisin with diabetic retinopathy (DR). A total of 233 healthy and adults participated in this study. Participants were divided into four categories: a healthy control group and an age-match subset of patients with type 2 diabetes; a positive control group of patients with type 2 diabetes not affected by DR (No DR); and patients with type 2 diabetes affected by DR (non-proliferative DR (NPDR) and proliferative DR (PDR)). Plasma samples were quantified for Irisin measurement, lipid profile and HbA1c. Comparison of the age-matched groups of healthy controls and patients with type 2 diabetes revealed lower Irisin plasma level in type 2 diabetes group. Analyses revealed negative correlations of Irisin to HbA1c and LDL levels and positive correlation to HDL level. Comparing Irisin level in No DR and DR groups revealed a higher level in No DR group and analysis per DR classification indicated higher Irisin level in NPDR group. Our results demonstrate not only correlation of plasma Irisin level with DR stages, but also significantly different Irisin level among them. This is promising in terms of researching Irisin as a potential associating marker for type 2 diabetes and DR development and progression.
Keywords: irisin; diabetes; diabetic retinopathy; metabolism; adipose tissue